Influence of age, fatness and education on variability of some traits in adult men - Wich, Jerzy (Anthropological Review, 1984)
The present study is based on cross-sectional material collected by Lower- -Silesian Center of Medical Diagnostics in Wrocław (1977 - 78). The analysis was carried out only on a part of that material, namely men aged 30-60 (N=786), divided on five age groups 30, 40, 50, 55 and 60 years old (mid-classes of the following age intervals 29, 30, 31; 39, 40, 41 and so on). Fatness was estimated on the base of thickness of subscapular skin fold. All individuals were divided on two groups only: with “low” (below of 40-th centile), and: “high” fatness (above of 60-th centile). The same procedure took place in relation to. education of investigated men All individuals were divided on two extreme groups too: with university, ‘and elementary or vocational education. The following traits were analysed: body height, body weight, systolic and diastolic blood pressure, vital lung capacity, erythrocytes, hemoglobins, the level in blood of calcium, glucose and cholesterol. The material was elaborated by means of the method of three-factorial nal of variance. The findings demonstrate Sonitvely that age, fatness and education, exert very significant .influence on, variability of the traits. Increased age is associated with increased body weight, systolic and. diastolic blood. pressure, glucose and cholesterol in blood. Fatness plays also an important role. The systolic and diastolic blood pressure, number of erythrocytes, and hemoglobins, glucose, cholesterol in blood, distinctly increase. with increasing “obesity” of men. A strong interdependence between arterial blood pressure and cholesterol was found. Educational status which reflects to some extent the socio-economic conditions, mode of life, type of work (physical or intellectual), produced many differences between more or less educated men. In general the men with university education are. taller, they have lower systolic blood pressure, and lower level of hemoglobins, calcium and glucose in blood, in compare with less educated men.